A person with diabetes as a patient - basic rules of conduct - Prylińska, Monika; Husejko, Jakub; Wąsicki, Mariusz; Modrzejewski, Mateusz; Szewczak, Dorota; Lamtych, Martyna; Osiak, Joanna; Bryfczyńska, Marta; Trawka, Paulina; Rogala, Dorota; Kwietniewska, Milena; Kędziora-Kornatowska, Kornelia (Journal of Education, Health and Sport, 2019)
BACKGROUND: Diabetes is very widespread disease. More and more patients suffer from hyperglycaemia and low levels of insulin because of obesity, aging and wrong diet. The most important in treatment based on health condition is to normalize glucose level. It is recommended to treat patients to avoid many complications of hyperglycaemia, e.g. cardiovascular diseases, stroke episodes, neuropathy or nephropathy. The most common cause of death are cardiovascular problems and renal failure.MATERIAL AND METHODS: A proper review of published literature provide to define laboratory indexes, risk factors, complications to precise methods of treatment among patients with diabetes.RESULTS: The problem of growing number of people suffering from diabetes is an important issue to find solutions to conduct their treatment. Basic method is a change of diet and body loss. The most important medicament in treatment is metformin. To achieve the best results of conducting therapy should be extended by pioglitazone or liraglutide. Also addition of aspirin lower dyslipidemia problems. Such a combination provides to minimise side effects of sickness.CONCLUSIONS: Number of people suffering from DM is still and will be growing over the next years. It is significant to diagnose these people because untreated diabetes provides to many complications e.g. stroke or acute coronary syndrome. It is important to examine patients correctly what allows to turn on correct treatment. Basic standards in treatment should contain lower glucose levels, avoid complications to enhance life quality. . Expanded therapy is also concentrated on hypertension, acidosis and ketoacidosis coma to obtain beneficial effects.